Navigating logistics currents towards business success. (2024)
In this interview, we spoke with Edisson Patiño Marín, whose career in the logistics field has been a source of inspiration and a role model for many. With a career spanning two decades, immersed in the world of logistics. Edisson has forged a path to excellence, with a unique combination of skills, strategic vision and unwavering dedication to achieving success. Its impact on the business sector, especially in the logistics field, has made it a benchmark in the industry.